Threshold trapdoor functions and their applications. (1st March 2020) - Tu, Binbin; Chen, Yu; Wang, Xueli
Abstract : The authors introduce a new cryptographic primitive named threshold trapdoor function (TTDF). TTDF is a threshold version of the trapdoor function. Its master trapdoor can be split into many pieces, and a quorum of shared trapdoors can be used to invert the function. TTDF holds one‐wayness, even if exposing part of shared trapdoors. Based on TTDF, they give generic constructions of threshold encryption under adaptive corruption model and revocation encryption. Then, they show TTDF can be instantiated under the decisional Diffie‐Hellman assumption and the learning with errors assumption. By combining the instantiations of TTDF with the generic constructions, they obtain threshold and revocation encryptions which compare favourably over existing schemes. The experimental results show that their proposed schemes are practical.